Analysis of the clinical efficacy of CCBs in patients with severe fever with thrombocytopenia syndrome combined with hypertension - Ziruo Ge; Chenxi Zhao; Yanli Xu; Xiaoyu Xue; Wei Pan; Wei Zhang; Zhihai Chen; Ling Lin; Di Tian (Virology Journal)
Abstract Background Calcium channel blockers (CCBs), commonly used in the treatment of various cardiovascular diseases, have shown promising potential in inhibiting the formation of viral inclusion bodies by lowering the level of intracellular Ca2+, thereby reducing viral replication. We conducted a retrospective single-center cohort study of SFTS patients with hypertension to assess the impact of CCB therapy on SFTS. Methods SFTS patients with hypertension treated in Qishan Hospital of Yantai from May 1, 2018, to December 31, 2022, were included. According to the admission criteria, 94 patients with SFTS were divided into the CCBs group (N = 30) and the control group (patients who took other antihypertensive drugs) (N = 64). We observed the severity of the disease, fatality rate, nucleic acid conversion time, nucleic acid’s positive rate, and the clinical improvement of the two groups. The effects of different CCBs on nucleic acid conversion were evaluated. Results There was a significant difference in the severity rate between the CCBs and control groups (63.3% vs. 82.8%, P = 0.038). The time of nucleic acid conversion in the CCBs group was significantly shorter than in the control group (P = 0.001). The nucleic acid negative conversion curve differed between the two groups (Log Rank P = 0.010), and the CCBs group was better. The frequency of vomiting and nervous system symptoms in the CCBs group was significantly lower than in the control group (P = 0.049,0.038), and the platelet level was significantly higher in the former than in the latter (P = 0.015). The conversion rate of nucleic acid in patients taking nifedipine was significantly higher than that in patients taking other CCBs (p = 0.036). Conclusions Our research indicates that CCBs may aid in decreasing disease severity, easing clinical symptoms, and potentially slowing the advancement to severe illness in patients with SFTS.